10Be surface exposure dating of the last deglaciation in the Aare Valley, Switzerland - Wüthrich, Lorenz (2018)
The combined Rhone and Aare Glaciers presumably reached their last glacial maximum (LGM) extent on the Swiss Plateau prior to 24 ka. Two well-preserved, less extensive moraine stades, the Gurten and Bern Stade, document the last deglaciation of the Aare Valley, yet age constraints are very scarce. In order to establish a more robust chronology for the glacial/deglacial history of the Aare Valley, we applied 10Be surface exposure dating on eleven boulders from the Gurten and Bern Stade. Several exposure ages are of Holocene age and likely document post-depositional processes, including boulder toppling and quarrying. The remaining exposure ages, however yield oldest ages of 20.7 ± 2.2 ka for the Gurten Stade and 19.0 ± 2.0 ka for the Bern Stade. Our results are in good agreement with published chronologies from other sites in the Alps.